2009
DOI: 10.1093/intimm/dxn139
|View full text |Cite
|
Sign up to set email alerts
|

A novel adjuvant, the general opioid antagonist naloxone, elicits a robust cellular immune response for a DNA vaccine

Abstract: While many adjuvants have been discovered and used in research, only a few adjuvants have been permitted for use with human vaccination. We have previously shown that the administration of naloxone (NLX), a general opioid antagonist, during infection with a non-virulent strain of herpes simplex virus type 1 (HSV-1) could enhance protection against HSV-1 challenge. Here, the adjuvant activity of NLX has been evaluated using a DNA vaccine for HSV-1 as a model. BALB/c mice were divided into four groups; for exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 52 publications
5
37
3
Order By: Relevance
“…The IFN-γ cytokine is an indicative of Th1 cellular immune responses and the induction of TCD8 + cells that have a key role in control and elimination of viral infections [18]. Many studies have shown the importance of IFN-γ in the control of viral infection [19]. Ullum et al [20] have measured the amount of IFN-γ in healthy, HIV-infected and AIDS patients and have shown that a decrease in IFN-γ was significantly correlated with progression to AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…The IFN-γ cytokine is an indicative of Th1 cellular immune responses and the induction of TCD8 + cells that have a key role in control and elimination of viral infections [18]. Many studies have shown the importance of IFN-γ in the control of viral infection [19]. Ullum et al [20] have measured the amount of IFN-γ in healthy, HIV-infected and AIDS patients and have shown that a decrease in IFN-γ was significantly correlated with progression to AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, vaccination against intracellular infection requires strong Th1 responses, and Freund's adjuvant can provide it, but the major obstacle is that it is not approved for human use. One of the best food and drug administration (FDA) approved vaccine adjuvants is aluminum salt (Alum), which mostly enhances Th2-specific responses (16). Currently, the standard HBV vaccine contains 20 microgram of hepatitis B surface antigen (HBsAg) in combination with 0.5 milligram of aluminum salt as an adjuvant (17).…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism of immunostimulating effect of naloxone is poorly understood. Fortunately, naloxone is a well-tolerated drug considering toxicity and adverse effects, and it is also FDA approved (16,20,22,23). During the last decade, many studies have used this agent as adjuvant in the formulation of different vaccines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adjuvants used in combination or mixture with vaccines by various mechanisms improve immune responses. 10,11 Such adjuvants are microbial product which bind to the Toll like receptors and induce inflammation. The microbial products that bind to the TLR5 is flagellin (FliC).…”
Section: Introductionmentioning
confidence: 99%